Traditional music sounds in harmony with nature - Koehler, Robert; Byeon Ji-yeon; Jin-hyuk, Lee; Mohuat, Colin A.; Yeon-ok, Jang; Eun-ji, Shin (Seoul Korea Foundation Seoul Selection, 2011)
Examines the development of Korean traditional music through its unique characteristics, wide variety of genres, dramatic history, and some of its influential performers.
"The content of this series is based on the material published in Koreana, the Korea Foundation's full-color quarterly featuring in-depth coverage of various aspects of Korea's cultural themes"--cover flap
Includes bibliographical references (pages 106-107).
Keywords: Music -- Korea -- History and criticism; Songs, Korean -- Korea -- History and criticism